INTERVENSI DAN BIMBINGAN EDUKASI KESEHATAN REPRODUKSI SEKSUAL REMAJA SEBAGAI PENCEGAHAN HIV AIDS DI KAMPUNG KB SERUMPUN KELURAHAN SINDANGJAYA MANDALAJATI KOTA BANDUNG - Sisca Lestari; Fajar Meihadi (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2024)
This service focuses on adolescent sexual reproductive health education in the Serumpun Quality Family Village Community, Sindangjaya Village, Mandalajati District. The approach used is based on community assets with the Asset Based Community Development (ABCD) method, which aims to provide correct information and increase adolescent knowledge about sexual reproductive health, and the dangers of risky behavior. This strategy not only encourages increasing knowledge but is expected to prevent the transmission of HIV and AIDS, especially among adolescents. The expected result is that adolescents have knowledge of reproductive health so that they stay away from risky behavior, thereby preventing the transmission of HIV and AIDS. This service shows that there is an increase in understanding and knowledge of adolescents about sexual reproductive health to prevent HIV and AIDS.